2018
DOI: 10.1155/2018/8129218
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Keratin/Alginate Blend Microparticles

Abstract: The water-in-oil (W/O) emulsification-diffusion method was used for construction of keratin (Ker), alginate (Alg), and Ker/Alg blend microparticles. The Ker, Alg, and Ker/Alg blend solutions were used as the water phase, while ethyl acetate was used as the oil phase. Firstly, different concentrations of Ker solution was used to find suitable content. 1.6% w/v Ker solution was blended with the same concentration of the Alg solution for further microparticle construction. Results from scanning electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The microparticles presented different shapes, from spherical to bowl-like and from porous to hollow, with varying sizes with the blend ratios. They reported that the interaction between functional groups of keratin (amino groups) and alginate (hydroxyl groups) was the main factor for both β-sheet structure and T d values of the microparticles, with both properties increasing with increasing the alginate content [294].…”
Section: Alginatementioning
confidence: 99%
“…The microparticles presented different shapes, from spherical to bowl-like and from porous to hollow, with varying sizes with the blend ratios. They reported that the interaction between functional groups of keratin (amino groups) and alginate (hydroxyl groups) was the main factor for both β-sheet structure and T d values of the microparticles, with both properties increasing with increasing the alginate content [294].…”
Section: Alginatementioning
confidence: 99%
“…In addition, a signi cant decrease in the intensity of the COO functional group at 1409 cm − 1 is observed in the keratin-alginate spectra compared to pure alginate, further supporting the hypothesis of complex formation between oppositely charged moieties in the keratin-alginate system. The band around 1020 cm − 1 disappears for keratin-alginate, illustrating possibility of electrostatic interaction between keratin and alginate and con rming successful crosslinking and particle formation [40].…”
Section: Micro/nano Keratin-based Particlesmentioning
confidence: 89%
“…Numerous studies have been dedicated to the use of keratin extracted from sheep wool for wound healing, tissue engineering, controlled release drugs or cosmetics. The efficiency of biomaterials made from keratin extracted from wool or hair on cell proliferation and adhesiveness is due to the presence of amino acid sequences: leucineaspartic acid -valine (LDV) and glutamic acid -aspartic acid -serine (EDS), self-assembly properties and biocompatibility [14][15][16][17][18]. Clinical tests with keratin-based products (keragel, keramatrix) have shown improvements in tissue surgery [19], foot ulcer [20] and bullous epidermolysis, a genetic disorder [21].…”
Section: Introductionmentioning
confidence: 99%